Secondary Metabolites from the Endophytic Fungus Xylaria sp. hg1009 - Rong Chen; Jian-Wei Tang; Xing-Ren Li; Miao Liu; Wen-Ping Ding; Yuan-Fei Zhou; Wei-Guang Wang; Xue Du; Han-Dong Sun; Pema-Tenzin Puno (Natural Products and Bioprospecting, 2018)
Abstract A detailed chemical investigation of the secondary metabolites produced by the endophytic fungus Xylaria sp. isolated from the stems of Isodon sculponeatus afforded six new compounds, xylariahgins A–F (1–6), two new natural products (7 and 8), along with two known compounds (9 and 10) (Fig. 1). The structures of all compounds were unambiguously established by analyzing their spectroscopic data or referring to pertinent literature. Compounds 1–8 were tested for their cytotoxic activity against five human tumor cell lines.